Examining the intersection of child protection and public housing: development, health and justice outcomes using linked administrative data - John W Lynch; Emma Baker; Alicia Montgomerie; Catia Malvaso; Rhiannon Megan Pilkington (BMJ Open)
Objective We described development, health and justice system outcomes for children in contact with child protection and public housing.Design Descriptive analysis of outcomes for children known to child protection who also had contact with public housing drawn from the South Australian (SA) Better Evidence Better Outcomes Linked Data (BEBOLD) platform.Setting The BEBOLD platform holds linked administrative records collected by government agencies for whole-population successive birth cohorts in SA beginning in 1999.Participants This study included data from birth registrations, perinatal, child protection, public housing, hospital, emergency department, early education and youth justice for all SA children born 1999–2013 and followed until 2016. The base population notified at least once to child protection was n=67 454.Primary outcome measure Contact with the public housing system.Secondary outcome measures Hospitalisations and emergency department presentations before age 5, and early education at age 5, and youth justice contact before age 17.Results More than 60% of children with at least one notification to child protection had contact with public housing, and 60.2% of those known to both systems were known to housing first. Children known to both systems experienced more emergency department and hospitalisation contacts, greater developmental vulnerability and were about six times more likely to have youth justice system contact.Conclusions There is substantial overlap between involvement with child protection and public housing in SA. Those children are more likely to face a life trajectory characterised by greater contact with the health system, greater early life developmental vulnerability and greater contact with the criminal justice system. Ensuring the highest quality of supportive early life infrastructure for families in public housing may contribute to prevention of contact with child protection and better life trajectories for children.